Quantitative Thermal Testing Profiles as a Predictor of Treatment Response to Topical Capsaicin in Patients with Localized Neuropathic Pain. (21st February 2017) - Serrano, A.; Torres, D.; Veciana, M.; Caro, C.; Montero, J.; Mayoral, V.
Abstract : There are no reliable predictors of response to treatment with capsaicin. Given that capsaicin application causes heat sensation, differences in quantitative thermal testing (QTT) profiles may predict treatment response. The aim of this study was to determine whether different QTT profiles could predict treatment outcomes in patients with localized peripheral neuropathic pain (PeLNP). We obtained from medical records QTT results and treatment outcomes of 55 patients treated between 2010 and 2013. Warm sensation threshold (WST) and heat pain threshold (HPT) values were assessed at baseline at the treatment site and in the asymptomatic, contralateral area. Responders were defined as those who achieved a > 30% decrease in pain lasting > 30 days. Two distinct groups were identified based on differences in QTT profiles. Most patients (27/31; 87.1%) with a homogenous profile were nonresponders. By contrast, more than half of the patients (13/24, 54.2%) with a nonhomogenous profile were responders (p = 0.0028 ). A nonhomogenous QTT profile appears to be predictive of response to capsaicin. We hypothesize patients with a partial loss of cutaneous nerve fibers or receptors are more likely to respond. By contrast, when severe nerve damage or normal cutaneous sensations are present, the pain is likely due to central sensitization and thus not responsive to capsaicin. Prospective studies with larger patient samples are needed to confirm this hypothesis.